Musical borrowing in hip-hop music: theoretical frameworks and case studies - Williams, Justin A. (2010)
'Musical borrowing in hip-hop' begins with a crucial premise: the hip-hop world, as an imagined community, regards unconcealed intertextuality as integral to the production and reception of its artistic culture. In other words, borrowing, in its multidimensional forms and manifestations, is central to the aesthetics of hip-hop. This study of borrowing in hip-hop music, which transcends narrow discourses on 'sampling' (digital sampling), illustrates the variety of ways that one can borrow from a source text or trope, and ways that audiences identify and respond to these practices. Another function of this thesis is to initiate a more nuanced discourse in hip-hop studies, to allow for the number of intertextual avenues travelled within hip-hop recordings, and to present academic frameworks with which to study them. The following five chapters provide case studies that prove that musical borrowing, part and parcel of hip-hop aesthetics, occurs on multiple planes and within myriad dimensions.